LOVE IN THE LYRICS OF SAPPHO AND MARINA TSVETAEVA: A COMPARATIVE ANALYSIS (Scientific journal of the Fergana State University, 2026)
This article presents a comparative analysis of the love poetry by the ancient Greek poetess Sappho and the Russian Silver Age poetess Marina Tsvetaeva, focusing on their characteristic themes of love for women. The study examines the biographical and cultural backgrounds that influenced each poetess's work, as well as the main motifs and figurative devices they used to convey experiences of love. A detailed analysis of specific poetic fragments by Sappho and Tsvetaeva is conducted, illustrating the nature of relationships and feelings of their lyrical heroines. The article compares the features of their poetic styles: Sappho's use of mythological folklore and natural symbolism, and Tsvetaeva's inner emotional modernism. The study demonstrates that both Sappho and Tsvetaeva perceived love as an all-encompassing force, yet approached its depiction differently, influenced by the peculiarities of their respective eras and personal experiences.